2020
DOI: 10.1590/0074-02760200303
|View full text |Cite
|
Sign up to set email alerts
|

In vitro-induction of metronidazole-resistant Giardia duodenalis is not associated with nucleotide alterations in the genes involved in pro-drug activation

Abstract: Giardiasis is an infectious disease caused by Giardia duodenalis. The pro-drug metronidazole (MTZ) is the first-line treatment for giardiasis. Parasite's proteins as pyruvate:ferredoxin oxidoreductase (PFOR), ferredoxin (Fd), nitroreductase-1 (NR-1) and thioredoxin reductase (TrxR) participate in MTZ activation. Here, we showed Giardia trophozoites long-term exposed to MTZ presented higher IC 50 than controls, showing the drug influenced the parasite survival. That reduction in MTZ's susceptibility does not se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Several conclusions can be drawn from the available data on antimicrobial resistance in G. duodenalis . The recorded multiple realizability of resistance, which can be mediated by various factors influencing the expression of multiple effector proteins without specific target gene mutations [ 62 ], is most likely due to epigenetic or posttranslational modifications [ 44 , 46 , 48 , 52 , 70 ] and does not require unambiguously identifiable patterns in proteomic assays [ 55 ]. Based on these findings including the results of comparative proteomics [ 55 ], it is highly unlikely to assume that rapid and easy-to-perform molecular assays for the detection of antimicrobial resistance will be available in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several conclusions can be drawn from the available data on antimicrobial resistance in G. duodenalis . The recorded multiple realizability of resistance, which can be mediated by various factors influencing the expression of multiple effector proteins without specific target gene mutations [ 62 ], is most likely due to epigenetic or posttranslational modifications [ 44 , 46 , 48 , 52 , 70 ] and does not require unambiguously identifiable patterns in proteomic assays [ 55 ]. Based on these findings including the results of comparative proteomics [ 55 ], it is highly unlikely to assume that rapid and easy-to-perform molecular assays for the detection of antimicrobial resistance will be available in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Matching the abovementioned, metronidazole resistance induced by long-term growth of G. duodenalis with sublethal metronidazole doses can occur completely without mutations in metronidazole resistance-associated genes like pfor, fd, nr-1 or trxr [ 62 ]. Nevertheless, some associations have been described.…”
Section: Hints For Genetic Versus Epigenetic Determinants Of Resistance In G Duodenalismentioning
confidence: 99%
“…Giardia spp. possess numerous potential sources of their activation, such as PFOR, ferredoxin, thioredoxin reductase, and several nitroreductases ( [125,290,291], and references therein). However, their individual contributions to the action of particular drugs remain a matter of debate.…”
Section: Role Of Bioreductive Processes In Antibacterial and Antiparasitic Action Of Nitroaromaticsmentioning
confidence: 99%
“…On the other hand, an American study conducted recently reported that although T. vaginalis virus was detected in 40% of their study population, it had no influence in clinical manifestations, reinfections and MTZ resistance [192] . In addition, based on the results obtained from two recently conducted studies [193,194] , German reviewers [195] attributed MTZ resistance to over-expression of various effector molecules without specific target gene mutations, i.e., epigenetic or posttranslational modifications without a recognized pattern in proteomic assays. They hypothesized that these modifications had essential roles in the parasite DNA with more significant effects than mutational base exchange [195] .…”
Section: Drug Resistancementioning
confidence: 99%